2009
DOI: 10.1007/bf03395670
|View full text |Cite
|
Sign up to set email alerts
|

A First Test of the Implicit Relational Assessment Procedure as a Measure of Self-Esteem: Irish Prisoner Groups and University Students

Abstract: The study examined the Implicit Relational Assessment Procedure's (IRAP) validity as a computerized response-latency-based measure of implicit self-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
37
0
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 41 publications
8
37
0
4
Order By: Relevance
“…As expected, the IRAPSE showed a significant effect for the self-positive response bias as indexed by significant one-sample t-tests in all diagnostic groups (ps ≤ 0.001). This is in line with (1) previous SE IRAP effects (e.g., [40] and [41]) and (2) findings for the 'universality' of self-positive implicit biases (e.g., [37]). An odd-even split-half procedure (applying the Spearman-Brown formula) was used to assess the reliability of the IRAP [42].…”
Section: Preliminary Analysessupporting
confidence: 92%
“…As expected, the IRAPSE showed a significant effect for the self-positive response bias as indexed by significant one-sample t-tests in all diagnostic groups (ps ≤ 0.001). This is in line with (1) previous SE IRAP effects (e.g., [40] and [41]) and (2) findings for the 'universality' of self-positive implicit biases (e.g., [37]). An odd-even split-half procedure (applying the Spearman-Brown formula) was used to assess the reliability of the IRAP [42].…”
Section: Preliminary Analysessupporting
confidence: 92%
“…Before each new block began, the participants were informed that the previously correct and incorrect answers would be reversed. The order in which IRAP blocks were presented was not counterbalanced across participants because previous research has found that this variable does not interact significantly with the critical IRAP effect (e.g., McKenna et al, 2007;Power et al, 2009;Vahey et al, 2009).…”
Section: Methodsmentioning
confidence: 99%
“…As predicted, response latencies were shorter for consistent than for inconsistent trials (e.g., participants responded more quickly to Unpleasant-Hate-Similar than to Unpleasant-Hate-Opposite). This basic IRAP effect has now been replicated across a small number of other studies, which have shown that the IRAP (a) compares well with the IAT as a measure of individual differences (Barnes-Holmes, Murtagh, Barnes-Holmes, & Stewart, in press; Barnes-Holmes, Waldron, , (b) is not easily faked (McKenna, Barnes-Holmes, Barnes-Holmes, & Stewart, 2007), (c) may be used as a measure of implicit self-esteem (Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009), and (d) produces effects that clearly diverge from those obtained from explicit measures when targeting socially sensitive attitudes (Power, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009).…”
mentioning
confidence: 99%
“…The first such study assessed self-esteem in both undergraduates and convicted prisoners. There were two groups of prisoners, one set residing in the main block of a medium-security prison and another set in a privileged, lower security "open area" of the prison (Vahey, Barnes-Holmes, Barnes-Holmes, & Stewart, 2009). Trials consisted of a sample relation ("similar" or "opposite") presented with positive and negative attributes (e.g., "good" and "bad").…”
Section: Research Using the Irapmentioning
confidence: 99%
“…The studies used the sample phrases "I am" and "I am not," as these reflect the natural viewpoint of the participant and also made the IRAP easier to administer, given that individual participants' names did not need to be programmed into the task. Much of the research conducted on the implicit measurement of self-esteem includes two categories (or samples): one that reflects the self and one that reflects the other (e.g., Vahey et al, 2009). These implicit measures, therefore, assess both attitudes toward the self and attitudes toward others (Karpinski, 2004;Yamaguchi et al, 2007) or, in the case of the IRAP, relational responding in regard to the self and with respect to someone (or some concept) outside of the self.…”
Section: Purpose Of Current Studiesmentioning
confidence: 99%